The Effect of Tax Avoidance and Agency Costs on Company Value with Profitability as a Mediating Variable - Agustin, Reni Cahya; Ria; Digdowiseiso , Kumba (CV ODIS, 2023)
This study examines the effect of tax avoidance and agency cost on company value by using profitability as a mediation variable. The independent variables used in this study are tax avoidance as measured by Cash Effective Tax Rate (CETR) and agency cost using the STA (Sales to Total Equity) ratio. The dependent variable in this study is the company's value measured using price-to-book value (PBV). Then the variable for the mediating variable is profitability which is measured using the ROA (Return on Assets) ratio. This study replicates the research conducted by Enggar Adityamurti, and Imam Ghozali, 2017 using secondary data of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021—test analysis using multiple analysis regression analysis model. The results of this study show that tax avoidance has a significant and positive effect on company value. Then, profitability can mediate the relationship between tax avoidance and agency cost to company value